2014
DOI: 10.7202/1027837ar
|View full text |Cite
|
Sign up to set email alerts
|

Tableau clinique des personnes cyberdépendantes demandant des services dans les centres publics de réadaptation en dépendance au Québec : étude exploratoire

Abstract: À ce jour, il n’existe aucun consensus quant aux critères diagnostiques d’une dépendance à Internet (Hinic, 2011 ; Tonioni et al., 2012 ; Weinstein et Lejoyeux, 2010). Pourtant, des personnes s’autodéclarent cyberdépendantes et réclament des soins dans les centres de réadaptation en dépendance (CRD) au Québec. Ces admissions ont amené l’Agence de la santé et des services sociaux de Montréal à demander la réalisation d’une étude descriptive sur la cyberdépendance.Objectifs : Décrire les caractéristiques sociodé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…[5][6][7][8][9][10] Despite these debates, several studies have reported IA prevalences oscillating between 0.6% and 26.7%. 4,[10][11][12][13][14][15][16][17][18] These sizable variations in the prevalences-depending on the studies, the countries, samples, and the evaluation criteria 10,19,20 -are of note.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10] Despite these debates, several studies have reported IA prevalences oscillating between 0.6% and 26.7%. 4,[10][11][12][13][14][15][16][17][18] These sizable variations in the prevalences-depending on the studies, the countries, samples, and the evaluation criteria 10,19,20 -are of note.…”
Section: Limitationsmentioning
confidence: 99%
“…4,12,14 There are presently no data available concerning IA problems among adolescents in the province of Quebec. 19 These data are of interest considering that the cultural differences associated with young Quebecers may have an impact on Internet use. 21,22 Furthermore, numerous health practitioners wonder whether preventive intervention is needed.…”
Section: Limitationsmentioning
confidence: 99%
“…De fait, près de 35% des jeunes de l'échantillon rapportent des symptômes dépressifs importants, ce qui s'éloigne des taux observés dans la population générale (4,9%) 39 mais également de taux rapportés dans les études réalisées auprès d'étudiants et d'adultes en traitement pour l'UPI (5-10%). 12,40,41 De plus, plus de la moitié de l'échantillon a reçu un diagnostic de TDAH par leur médecin au cours de leur vie. Ce pourcentage est une fois de plus nettement supérieur aux taux rapportés chez les adolescents de la population générale (13%) 39 et dans les études réalisées auprès de personnes consultant pour leur UPI (7,1%-14%).…”
Section: Discussionunclassified
“…6,[11][12][13][14][15] Among the latter, relational consequences are the most commonly reported by adolescents and adults. 11,16,17 For example, more than half of adolescents in treatment for PIU reported having sought help because of the conflicts and difficulties that their Internet use created with their parents. 11 Similarly, more than half (53%) of adults with PIU claimed to have experienced marital difficulties, such as marital conflict, separation, and divorce.…”
Section: Introductionmentioning
confidence: 99%
“…They come in various forms, including physical, psychological, relational, occupational, academic, and financial 6,11–15 . Among the latter, relational consequences are the most commonly reported by adolescents and adults 11,16,17 . For example, more than half of adolescents in treatment for PIU reported having sought help because of the conflicts and difficulties that their Internet use created with their parents 11 .…”
Section: Introductionmentioning
confidence: 99%